Field Observation of Soil Displacements Resulting Due Unsupported Excavation and Its Effects on Proposed Adjacent Piles - Ala Nasir Al-Jorany, Prof. Dr.; Ghusoon Sadik Al-Qaisee, Ass. Lect. (Journal of Engineering, 2016)
Soil movement resulting due unsupported excavation nearby axially loaded piles imposes significant structural troubles on geotechnical engineers especially for piles that are not designed to account for loss of lateral confinement. In this study the field excavation works of 7.0 m deep open tunnel was continuously followed up by the authors. The work is related to the project of developing the Army canal in the east of Baghdad city in Iraq. A number of selected points around the field excavation are installed on the ground surface at different horizontal distance. The elevation and coordinates of points are recorded during 23 days with excavation progress period. The field excavation process was numerically simulated by using the finite element package PLAXIS 3D foundation. The obtained analysis results regarding the displacements of the selected points are compared with the field observation for verification purpose. Moreover, finite element analysis of axially loaded piles that are presumed to be existed at the locations of the observation points is carried out to study the effect of excavation on full scale piles behaviors. The field observation monitored an upward movement and positive lateral ground movement for shallow excavation depth. Later on and as the excavation process went deeper, a downward movement and negative lateral ground movement are noticed. The analyses results are in general well agreed with the monitored values of soil displacements at the selected points. It is found also that there are obvious effects of the nearby excavation on the presumed piles in terms of displacements and bending moments.